The Ergonomic Risk Evaluation of Work Posture for Oil Palm Harvest Workers in Large Plantations in East Kalimantan using SNI 9011:2021 - Pawitra, Theresia Amelia; Khairi, Rivki Al; Widada, Dharma (Journal of Integrated System, 2024)
Indonesia, as the world's largest palm oil producer, relies on contributions from smallholder farms, state plantations, and private estates. Despite its scale, much of the harvesting process remains manual, posing risks of musculoskeletal disorders due to non-ergonomic work postures. This study evaluated work postures in two plantations: PT DSN (private) and PTP XIII (state-owned) in East Kalimantan, involving 96 workers: 47 harvesters, 12 transporters, and 37 loose fruit collectors. The findings revealed that 83% of harvesters experienced neck pain, 75% of transporters of fresh fruit bunches (FFB) reported knee pain, and 95% of loose fruit collectors faced neck pain. Ergonomic Risk Factor analysis showed FFB transportation as the most hazardous activity (score 74), followed by harvesting (62) and loose fruit collection (55). The key contributors to these risks included body posture and manual material handling, with body posture contributing 58% to scores in loose fruit collection and FFB unloading. Proposed ergonomic improvements include holistic safe care for harvesters, tractor scissor lifts for FFB transport, and modified nut pickers for loose fruit collection. While these interventions promise to increase efficiency, productivity, and safety, success hinges on addressing challenges such as initial costs, worker training, and equipment adaptation to field conditions.